Speroff's clinical gynecologic endocrinology and infertility - Taylor, Hugh S.; Pal, Lubna; Seli, Emre (Wolters Kluwer, 2020)
"In the United States, approximately 15% of all couples will face fertility difficulties, many of whom will go on to a reproductive disorder diagnosis. OB/GYNs specialize in reproductive endocrinology & infertility through a fellowship track after their residency. Today there are approximately 500 reproductive endocrinologists in addition to 800 who are board-eligible. Written in a clear and concise voice, Clinical Gynecologic Endocrinology and Infertility provides a complete explanation of the female endocrine system and offers medical guidance for evaluation and treatment of common disorders"-- Provided by publisher.